2010
DOI: 10.1021/nn9014533
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Conductive and Photoluminescent DNA-Templated Polyindole Nanowires

Abstract: Polyindole (PIn) nanowires were formed on a lambda-DNA template by chemical oxidation of indole using aqueous FeCl3. The resulting nanowires are smooth, regular, conductive and had diameters in the range of 5-30 nm. These features allow them to be aligned by molecular combing and studied by scanned conductance microscopy, conductive AFM, and two-terminal I-V measurements. Using this combination of measurements, we find that the conductivity of PIn/DNA nanowires is between 2.5 and 40 S cm(-1) at room temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
102
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(117 citation statements)
references
References 47 publications
15
102
0
Order By: Relevance
“…DNA self‐assembly has attracted significant attention as it offers a bottom‐up manufacturing technique to provide efficient templates for the subsequent assembly of either organic or inorganic nanoelements such as metallic charged nanoparticles or streptavidin proteins . Surface modification of individual DNAs and their configurations is of crucial importance to develop nanoscale devices based on DNA‐templated assembly . In this context, the specific immobilization of a large number of DNA molecules on a solid substrate has progressed over the past years for many potential applications such as electronic, magnetic, optoelectronic, and sensors, in which DNA molecules are “addressable” only when they are highly ordered or stretched.…”
Section: Introductionmentioning
confidence: 99%
“…DNA self‐assembly has attracted significant attention as it offers a bottom‐up manufacturing technique to provide efficient templates for the subsequent assembly of either organic or inorganic nanoelements such as metallic charged nanoparticles or streptavidin proteins . Surface modification of individual DNAs and their configurations is of crucial importance to develop nanoscale devices based on DNA‐templated assembly . In this context, the specific immobilization of a large number of DNA molecules on a solid substrate has progressed over the past years for many potential applications such as electronic, magnetic, optoelectronic, and sensors, in which DNA molecules are “addressable” only when they are highly ordered or stretched.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to impressive alterations in optical as well as physico-chemical properties. Several conducting polymers viz polypyrrole (PPy), polyaniline, polythiophene, polyindole, polyethylenedioxy thiophene have been widely employed during the past few decades [9][10][11][12][13][14]. Among these conducting polymers, PPy has attracted great interest due to its ease of preparation, wide conductivity range (10 À2 to 10 4 S cm À1 ), satisfactory environmental stability and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…Moon et al (2010) also chemically polymerized polypyrrole nanowires using DNA as a template on a (3-aminopropyl)triethoxysilane modified silicon wafer with ammonium persulfate as an oxidant. Hassanien et al (2010) reported that polyindole nanowires were synthesized on a -DNA template by chemical oxidation of indole using FeCl 3 as an oxidant. Figure 3 shows AFM images of conducting polymer nanowires using DNA as a template.…”
Section: Soft Templatementioning
confidence: 99%
“…Figure 3 shows AFM images of conducting polymer nanowires using DNA as a template. (Dong et al, 2007); (b) DNA/polypyrrole nanowire (Moon et al, 2010); (c) DNA/polyindole nanowires aligned between Au electrodes (Hassanien et al, 2010).…”
Section: Soft Templatementioning
confidence: 99%